The Level of Enhancing Child Protection in the Digital World from the Perspective of Parents in Riyadh - Alkatheery, Kholoud Rashed (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to reveal the level of enhancing child protection in the digital world from the point of view of parents in Riyadh. Methods: The study employed a descriptive methodology to achieve its objectives. A scale was designed to measure the level of enhancing child protection in the digital world from the perspective of parents. The study's population comprised all parents of children enrolled in early childhood education in Riyadh. The scale was applied to a sample of 276 parents randomly selected. Results: The results indicated that the sample members somewhat agreed on the benefits of children using digital devices. Agreements prominently appeared in statements such as: "My child is proficient in using electronic devices," followed by "My child is competent in navigating the digital world." The results also revealed that the study's sample members were aware of the drawbacks of children's use of digital devices. Concerns were expressed in the following statements: "The digital world may contribute to decreased physical activity in children," followed by "Excessive use of the digital world can lead to addiction in children." Additionally, participants supported parental measures in the digital realm, particularly in instilling religious values and monitoring academic progress. Statistical analysis revealed significant differences in responses regarding both digital benefits and parental measures, favoring Nintendo devices when available for the child. Conclusions: In the light of these findings, the study recommended strengthening protection from negative effects when children use the digital world.